2022
DOI: 10.1001/jamanetworkopen.2021.42509
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Insurance Coverage for Acupuncture, 2010-2019

Abstract: This survey study examines US trends in insurance coverage for acupuncture from 2010 through 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…In terms of Traditional Chinese medicine treatment, it is not only to eliminate symptoms, but also to strengthen the righteousness and eliminate pathogenic factors, regulate the balance yin and yang. What's more, acupuncture treatment was not admitted to medical insurance in some western countries, which could cause an economic burden to patients (33,34). Based on the above reasons, acupuncture treatment was different between China and the Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of Traditional Chinese medicine treatment, it is not only to eliminate symptoms, but also to strengthen the righteousness and eliminate pathogenic factors, regulate the balance yin and yang. What's more, acupuncture treatment was not admitted to medical insurance in some western countries, which could cause an economic burden to patients (33,34). Based on the above reasons, acupuncture treatment was different between China and the Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…[ 42 ] The medical cost encountered by TCM users might be considerably higher in other locations across the world where TCM is not covered by the national health insurance and instead forms part of private health costs. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture, a traditional Chinese therapy, has a gradually increasing geographical coverage and application rate ( 13 ). The NIH Consensus Conference ( 14 ) and publications ( 15 , 16 ) have demonstrated that acupuncture can improve the neurological motor deficit symptoms and become an acceptable alternative method for stroke rehabilitation.…”
Section: Introductionmentioning
confidence: 99%